2015
DOI: 10.1080/10934529.2015.1055129
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of volatile organic compounds and particulate matter in a dental clinic and health risks to clinic personnel

Abstract: This study was conducted to assess (1) levels of volatile organic compounds (VOCs) and particulate matter (PM) in a dental clinic in southern Taiwan and (2) dental care personnel's health risks associated with due to chronic exposure to VOCs. An automatic, continuous sampling system and a multi-gas monitor were employed to quantify the air pollutants, along with environmental comfort factors, including temperature, CO2, and relative humidity at six sampling sites in the clinic over eight days. Specific VOC com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 15 publications
2
16
0
1
Order By: Relevance
“…Human density is a very effective factor in PM and microbial aerosol concentrations in the air of densely occupied wards, such as an educational environment in dental school. The PM 10 and PM 2.5 concentrations obtained in this study are comparable with the data reported by some studies (Helmis et al 2008 ; Hong et al 2015 ). Sotiriou et al ( 2008 ) demonstrated that the drilling actions during surgery in the dental office are related with the particles smaller than 0.5 μm and no significant levels of larger particles (larger than 1 μm) were correlated with these treatment actions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Human density is a very effective factor in PM and microbial aerosol concentrations in the air of densely occupied wards, such as an educational environment in dental school. The PM 10 and PM 2.5 concentrations obtained in this study are comparable with the data reported by some studies (Helmis et al 2008 ; Hong et al 2015 ). Sotiriou et al ( 2008 ) demonstrated that the drilling actions during surgery in the dental office are related with the particles smaller than 0.5 μm and no significant levels of larger particles (larger than 1 μm) were correlated with these treatment actions.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the increased PM levels were observed in the periodontics ward, which can be due to the treatment procedure used in this ward of the dental clinic. Scaling by high-speed dental handpieces, tooth extraction, and oral surgeries are possible main sources of PM levels (Hong et al 2015 ). On the other hand, the high numbers of patients, dental staff, and dental students may cause an increase in PM concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies intended to assess the dissemination of aerosol by measuring bacterial contamination in the dental operatory [9,17,18], only a handful of studies directly measured the aerosol's dissemination [19][20][21]. However, these studies either measured the aerosol level in the whole area of dental office which includes multiple dental chairs/operatories, or measured the generation of aerosols in a long period of time (ranged from a day to a week) [20,21]. In addition, some studies used manikin or extracted teeth instead of patients [12,19], which failed to simulate dental aerosols that contains a mixture of patient's saliva and fluid with compressed air and water.…”
Section: Discussionmentioning
confidence: 99%
“…During dental treatment procedures, dentists and all dental staff may expose to bioaerosols [4,5] and PMs [68]. Previous studies indicated that aerosols exposure was related to the risks of respiratory, liver, renal, and nervous systems dysfunction [911]. However, no study was evaluated the relationship between health effects of dental healthcare workers and aerosols exposure during dental treatment.…”
Section: Introductionmentioning
confidence: 99%
“…One study in the United States reported that dental procedures produced considerably more PM 0.3–0.5 (particulate matter 0.3–0.5 μm in size) (2.32×10 8 –3.74×10 8 particles/m 3 ) than those that were present in the background air (2.22×10 8 particles/m 3 ) [6]. Others have reported higher PM concentrations during dental therapy procedures than during non-working periods (i.e., indoor background) [6,7,1113].…”
Section: Introductionmentioning
confidence: 99%